Bibó István és Max Weber (Szociológiai Szemle, 2024)
The intellectual relationship between Bibó and Max Weber is observable in three areas. Having read Weber’s Protestant Ethics, young Bibó realised that it was impossibile to transform the bourgeoisie into a real elite because in mass societies with big social inequalities collecting wealth cannot be the sole criterion of meritocracy. Weberian Verstehen inspired him trough the synoptical legal sociology of his master, Barna Horváth, as synopsis is an eternal oscillation between Weberian Verstehen and Mannheimian Wissenssoziologie. Thirdly, Bibó adapted Weber’s approach of rationality adopting István Hajnal’s criticism on Weber: in Bibo’s eyes, merely Zweckrational exercise of power is a major obstacle o f the Entzauberung of politics.